Il contesto linguistico della letteratura italiana dell'emigrazione. Sondaggi (Atti del Sodalizio Glottologico Milanese, 2017)
The culture of the Italian immigrant experience worldwide has been characterized by daily dynamics of adaptations and transformations deeply shaping the processes of identity-formation. By looking at the diverse and decade-long linguistic metamorphoses we can start to reclaim the importance of a literary production too often overlooked (both in its âinstitutionalâ works and in its more personal autobiographical expressions) â and at the same time re-evaluate the complex creativity of its linguistic fabric. KEYWORDS: Italians in the U.S., Italian migration, Language and literature, Italian language abroad, Italian American poetry and fiction